2012
DOI: 10.1152/ajprenal.00278.2011
|View full text |Cite
|
Sign up to set email alerts
|

V-ATPase promotes transforming growth factor-β-induced epithelial-mesenchymal transition of rat proximal tubular epithelial cells

Abstract: The ubiquitous vacuolar H(+)-ATPase (V-ATPase), a multisubunit proton pump, is essential for intraorganellar acidification. Here, we hypothesized that V-ATPase is involved in the pathogenesis of kidney tubulointerstitial fibrosis. We first examined its expression in the rat unilateral ureteral obstruction (UUO) model of kidney fibrosis and transforming growth factor (TGF)-β1-mediated epithelial-to-mesenchymal transition (EMT) in rat proximal tubular epithelial cells (NRK52E). Immunofluorescence experiments sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…TGF-␤1 can induce epithelial-to-mesenchymal transition in renal epithelial cells as well as increased expression of a number of V-ATPase subunits, including B2, E, and c (39). TGF-␤1 treatment also stimulates V-ATPase activity and plasma membrane localization in these cells, and inhibition of V-ATPase activity blocks the TGF-␤1 induced epithelial-to-mesenchymal transition (39). Although the effect of TGF-␤ stimulation on a3 expression has not been evaluated, one possibility is that a3 overexpression promotes invasion in MCF10a cells by a similar mechanism as TGF-␤ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤1 can induce epithelial-to-mesenchymal transition in renal epithelial cells as well as increased expression of a number of V-ATPase subunits, including B2, E, and c (39). TGF-␤1 treatment also stimulates V-ATPase activity and plasma membrane localization in these cells, and inhibition of V-ATPase activity blocks the TGF-␤1 induced epithelial-to-mesenchymal transition (39). Although the effect of TGF-␤ stimulation on a3 expression has not been evaluated, one possibility is that a3 overexpression promotes invasion in MCF10a cells by a similar mechanism as TGF-␤ stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cao et al . () demonstrated that Atp6v1e2‐mediated pH change was involved in TGF‐β1‐induced EMT in rat renal tubular cells, which also plays a critical role in MR formation (Xu et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This feature requires the presence of adherens and tight junctions, cell structures that require the expression of cadherins, claudins and occludin proteins. Particularly important is the formation of the tight junction because this structure forms the boundary of two-dimensional diffusion of the apical and basal-lateral plasma membrane, which enables the polar distribution of uptake and efflux transporters (Cao et al, 2012). The current study assessed the expression of many members of these three classes of proteins.…”
Section: Discussionmentioning
confidence: 99%